Metafora Ontologis Dalam Novel Cala Ibi Karya Nukila Amal - Dwi Cahya, Ancha; Maharani Umaya, Nazla; Muhajir, Muhajir (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to describe and analyze the use of ontological metaphors in the novel Cala Ibi by Nukila Amal. Ontological metaphor is a type of conceptual metaphor that describes abstract concepts such as emotions, time, or ideas as concrete entities that can act like human beings. The research method used is descriptive qualitative with data collection techniques in the form of literature study, reading and note taking techniques. The main source of data in this research is the novel Cala Ibi itself, while the data are linguistic units (words, phrases, clauses and sentences) that contain ontological metaphors. The collected data are then analyzed and interpreted based on the narrative context in the novel. The results showed that from the 276 pages analyzed, a total of 63 data were found to be ontological metaphors. This finding proves that Cala Ibi not only presents a poetic narrative, but also contains a deep conceptual dimension through the use of metaphors. This study is expected to contribute to the field of literary studies, especially the cognitive semantic approach to contemporary Indonesian literary texts.